Postoperative outcomes after total hip arthroplasty in patients with Parkinson disease: A protocol of case control study. Issue 19 (May 2020) - Zhang, Yuerong; Xiong, Ke; Li, Ruizhen; Yang, Li
Abstract: Background: Parkinson disease (PD) is a progressive neuromuscular disease associated with bradykinesia, tremor, and postural instability. We aimed to compare outcomes and complications of total hip arthroplasty (THA) between patients with PD and those without. Methods: A single institution retrospective cohort from 2000 to 2018 was reviewed. PD patients were matched 1:2 with non-PD control patients for age, gender, American Society of Anesthesiologists score, and body mass index using a propensity score matching procedure. The primary outcome measures were postoperative complications and revision between PD and cohort groups. Secondary outcome measures were Harris Hip Score, hip range of motion, patient satisfaction, and surgery time. Univariable and multivariable logistic regression were used to determine the relationship between PD and surgical outcomes in the matched cohort. Results: Using prospectively collated data, we identified 35 PD patients after primary THA. A control cohort of 70 primary THA patients was matched. Conclusion: Our hypothesis was that PD would have adverse impact on complication rates, range of movement, or improvement in functional outcome after subsequent THA. Trial registration: This study protocol was registered in Research Registry (researchregistry5446).